2018
DOI: 10.1038/s41598-018-25317-8
|View full text |Cite
|
Sign up to set email alerts
|

Significantly increased low shear rate viscosity, blood elastic modulus, and RBC aggregation in adults following cardiac surgery

Abstract: Open heart surgeries are common for treating ischemic and heart valve disease. During cardiac surgery, cardiopulmonary bypass (CPB) can temporarily take over the function of heart and lungs. However, elevated red blood cell (RBC) aggregation may lead to the common side-effects such as microinfarction. We investigated blood physical properties changes and the correlation between blood microstructure, viscoelastic response and biochemical changes following surgery with CPB. We examined shear-rate dependent blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…Coronary artery blood flow is not at steady-state, making its viscosity inconstant. Furthermore, previous studies have reported a significant increase in blood viscosity during and after cardiac surgery 33 . Cardiac surgery can cause abnormal blood rheological characteristics that may be associated with lung dysfunction and endothelial damage 34 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Coronary artery blood flow is not at steady-state, making its viscosity inconstant. Furthermore, previous studies have reported a significant increase in blood viscosity during and after cardiac surgery 33 . Cardiac surgery can cause abnormal blood rheological characteristics that may be associated with lung dysfunction and endothelial damage 34 .…”
Section: Discussionmentioning
confidence: 93%
“…Cardiac surgery can cause abnormal blood rheological characteristics that may be associated with lung dysfunction and endothelial damage 34 . In addition, blood viscosity changes due to systemic inflammatory and thrombotic responses during cardiac surgery 33 . Although blood viscosity was measured twice during surgery and was divided into systolic and diastolic viscosity in this study, it changes continuously according to the blood flow during surgery, making it difficult to determine the real-time relationship between viscosity and TTFM.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery blood flow is not at steady-state, making its viscosity inconstant. Furthermore, previous studies have reported a significant increase in blood viscosity during cardiac surgery and after surgery [32]. Cardiac surgery can cause abnormal blood rheological characteristics that may be associated with lung dysfunction and endothelial damage [33].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac surgery can cause abnormal blood rheological characteristics that may be associated with lung dysfunction and endothelial damage [33]. In addition, blood viscosity changes due to systemic inflammatory and thrombotic responses during cardiac surgery [32]. Although the blood viscosity was measured twice during surgery and was divided into systolic and diastolic viscosity, blood viscosity changes according to the blood flow with continuous change during the surgery, making it difficult to determine the real-time relationship between viscosity and TTFM.…”
Section: Discussionmentioning
confidence: 99%
“…There are three main factors that can influence blood viscosity, namely hematocrit, erythrocyte aggregation and erythrocyte deformation [22]. All three factors can be altered by NP–erythrocyte interactions, which underlines the importance of carefully studying the influence of NPs on the critical functions of blood cells.…”
Section: Erythrocyte Function In Hemostasis and The Mechanisms Invmentioning
confidence: 99%